The Impact of the Disaster News on Social Capacity Building Against Disasters - Serhat Yılmaz (Doğal Afetler ve Çevre Dergisi, 2019)
Providing that, the continuum of social life is one of the most important aims of the preparedness against disasters, carrying individual risk reduction activities against disasters is vital for achieving this goal. However, increasing the awareness of a society under disaster risk can be realized with high costs and time. Mass media tools, especially newspapers and television which are widely used in daily life for accessing the information needed, are offering an advantage in order to decrease these high costs and are much faster. Within the scope of this study, the effectiveness of these mass media tools in the context of social capacity building on disasters has been examined. For this purpose, the contents of the Bodrum Earthquake’s (occurred on July 27th, 2017) news which were published in the first three most widely read newspapers in Turkey, and were broadcasted on the first three rated news programs, were analyzed by framing theory. After these analyses, the effects on the social capacity building against disaster are being questioned. As a result of the study, it has been revealed that the disaster news are generally being addressed with sensational perspective, and the advantages being offered by the mass media tools are not effectively utilized for creating awareness on individual preparedness activities.